AB0540 Diversity of Clinical Manifestations of Primary SjÖgren's Syndrome. (9th June 2015) - Sebastian, A.; Wiland, P.
Abstract : Background: Primary Sjögren's syndrome (pSS) is a systemic connective tissue disease which clinical picture may involve with its spectrum all the organs, especially salivary glands, lacrimal glands and musculoskeletal system. Extraglandular manifestations are present in 30-40% of patients. The prevalence of pSS in Europe is 0.2%. The whole symptoms of dryness occur most commonly many months after the onset of the disease. Objectives: The aim of this study was to assess the factors determining the variety of clinical picture in pSS including: age, the presence of antinuclear (ANA) and specific antibodies (SSA/SSB/Ro52), rheumatoid factor (RF), sedimentation rate (ESR), C-reactive protein (CRP), serum protein electrophoresis, serum immunoglobulin concentration and the intensification of organ changes in pSS. Methods: The study group consisted of 68 patients diagnosed with pSS. The control group consisted of 43 patients who were diagnosed for pSS due to dryness symptoms. Results: Anti-SSA antibodies were found in 82%, anti-Ro52 antibodies in 70% and anti-SSB antibodies in 69% of patients with pSS. The configuration of all three specific antibodies anti-SSA+SSB+Ro52 was found in 54%, anti-SSA+SSB in 15% and anti-SSA+Ro52 in 13% of patients. The presence of only anti-SSA or anti-SSB antibodies without any other specific antibodies was not confirmed. Taking into consideration the intensification of the eye, oral and vaginal dryness and the subjective feeling of fatigue in the group of patients with pSS and in the control group, the statistically significant difference between groups was found in the fatigue intensification (p=0.042). In patients with pSS the focus score was 2.2 and in the control group was 0.3. Among 30 patients in 20 (66%) of patients there were found changes in the lung tissue in the course of pSS what accounted for 29% of patients from the study group. There was found no association between the more common presence of anti-SSA, anti-SSB, anti-Ro52 antibodies and changes in HRCT. Focus score was significantly higher in patients with changes in the major salivary glands (p=0.02) and skin changes. Peripheral lymphadenopathy was found in 22% of patients with pSS, more often in young patients (p=0.04), with an abnormal level of RF (p=0.003) and higher titre of anti-Ro52 antibodies (p=0.01). Higher ESSDAI was associated with skin changes (p=0.002) and changes in parotid or submandibular gland (p=0.002). Conclusions: The concomitance of anti-SSA-SSB-Ro52 antibodies is characteristic of pSS. The higher titres of anti-SSA and anti-Ro52 antibodies are associated with lymphadenopathy and hypergammaglobulinemia. The higher titres of specific anti-SSB antibodies are associated with the development of protein dysfunctions. It is impossible to make a difference between the patients with pSS and a healthy population on the basis of the intensification of the subjective symptoms of dryness. Fatigue is more common in patients with pSS and may serve as a differentiating factor. The respiratory system is affected in about 30% of patients with pSS. Skin changes and changes in parotid or submandibular gland were more common in patients with higher ESSDAI score. Disclosure of Interest: None declared